An analysis of changing land use pattern and its effect on Umtrew Basin, Northeast India - Sharma, Pradip; Deka, Dhanjit; Saikia, Ranjan (Hungarian Geographical Bulletin, 2011)
Land use change is accelerating throughout Northeast India and is the cause of many environmental problems. The Umtrew is a major river that originates on the Meghalaya Plateau, flows down to the Assam Valley, and is one of the tributaries of the Brahmaputra (Roy, P.S. and Tomar, S. 2001). The Umtrew Basin covers an area of 1253.1 sq km, mostly in the foothills of the Meghalaya Plateau. Remote sensing and GIS techniques are used to explore the changing pattern of land use/land cover. The study employs satellite data from Landsat-MSS and IRS-1C LISS III for the years 1977, 1999, 2004 and 2007. Its aim is to formulate a plan/strategy for maintaining environmental quality.